Early suppression of immune response pathways characterizes children with prediabetes in genome-wide gene expression profiling - Elo LL; Mykkanen J; Nikula T; Jarvenpaa H; Simell S; Aittokallio T; Hyoty H; Ilonen J; Veijola R; Simell T; Knip M; Simell O; et al. (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2022)
Type 1 diabetes (T1D) is caused by autoimmune destruction of insulin-producing pancreatic p cells in the islets of Langerhans. Although defects in various T cell subsets have been linked to the disease pathogenesis, mechanisms initiating or enhancing the autoimmunity in prediabetes remain poorly understood. To unravel genes and molecular pathways affected by the diabetes-associated autoimmunity, we investigated transcriptomic profiles of prospective whole-blood samples from children who have developed T1D-associated autoantibodies and eventually clinical T1D. Gene-level investigation of the data showed systematic differential expression of 520 probesets. A network-based analysis revealed then a highly significant down-regulated network of genes involved in antigen presentation as well as T-cell receptor and insulin signaling. Finally, detection of dynamic changes in the affected pathways at the early or late phases of autoimmunity showed down-regulation of several novel T1D-associated pathways as well as known key components of immune response. The longitudinal genome-wide data generated in the present study allows the detection of dynamic changes relevant to the disease that may be completely missed in conventional cross-sectional studies or in genome-wide association studies. Taken together, our analysis showed systemic high-level repression of immune response pathways associated with T1D autoimmunity. (C) 2010 Elsevier Ltd. All rights reserved.